Generation and enhancement of sum sideband in a parity-time-symmetric optomechanical system. (24th June 2020) - Rao, Shi; Huang, Yanxia
Abstract: This paper studies sum sideband generation in a parity-time ( PT )-symmetric optomechanical system, where an active cavity is coupled to the passive cavity of a general optomechanical system. We find that the upper and lower sum sideband generation efficiencies can be greatly enhanced by the introduction of the gain cavity. Furthermore, when the coupling coefficient and gain–loss ratio are near the exceptional point, the upper sum sideband amplitude is larger than that of the probe fields. This paper also investigates the optimal matching conditions for upper and lower sum sideband generation in the PT -symmetric phase, the broken PT -symmetric phase and at the exceptional point, respectively. As a result, new matching conditions are discovered and the appearance of these new matching conditions is ascribed to eigenfrequency splitting. The enhanced sum sideband can be applied to coherent light manipulation, quantum information processing and sensitive quantum metrology.